Children’s attitudinal reactions to TV advertisements The African experience - Gbadamosi, Ayantunji; Hinson, Robert E.; Tukamushaba, Eddy K.; Ingunjiri, Irene (International Journal of Market Research, 2012)
This paper is aimed at exploring African children’s attitudinal reactions to television advertisements. A total of 65 children from four African countries – Ghana, Nigeria, Kenya and Uganda – participated in 12 focus group discussions on the subject matter. Findings suggest that they like television advertising in relation to its entertainment features – especially when the messages feature children characters, cartoons, music, celebrities and humour – and those promoting foods. They also derive excitement from advertising messages that are presented in Pidgin language and/or humorously integrated with local languages. However, they have an aversion to messages that terrify them and those they consider boring. This paper supplements the existing literature on the attitudes of children to advertising, but from Africa as a different contextual platform. It also suggests directions for the effective use of marketing communications strategies in relation to television advertising for marketers and other bodies with special roles in communicating with children such as government agencies and NGOs.
Keywords: Children; reactions; African experience